2023
DOI: 10.1101/2023.03.17.533028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory cortical ensembles exhibit differential coupling to ripples in distinct hippocampal subregions

Abstract: Cortical neurons activated during recent experiences often reactivate with dorsal hippocampal CA1 sharp-wave ripples (SWRs) during subsequent rest. Less is known about cortical interactions with intermediate hippocampal CA1, whose connectivity, functions, and SWRs differ from those of dorsal CA1. We identified three clusters of visual cortical excitatory neurons that are excited together with either dorsal or intermediate CA1 SWRs, or suppressed before both SWRs. Neurons in each cluster were distributed across… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…They found that sharp-wave ripples coincided with a transient, cortex-wide increase in functional connectivity with the hippocampus. Jeong et al, 2023 examined the topography of this functional connectivity and found that distinct but intermingled classes of visual cortex neurons were preferentially modulated by ripples originating in dorsal hippocampus, while others were more coupled to ripples in intermediate hippocampus. Purandare and Mehta, 2023 analyzed the responses of hippocampal neurons to natural movies and found that many displayed highly selective ‘movie fields’ that were often as robust as those of neurons in visual cortex.…”
Section: Three Families Of Use Casesmentioning
confidence: 99%
“…They found that sharp-wave ripples coincided with a transient, cortex-wide increase in functional connectivity with the hippocampus. Jeong et al, 2023 examined the topography of this functional connectivity and found that distinct but intermingled classes of visual cortex neurons were preferentially modulated by ripples originating in dorsal hippocampus, while others were more coupled to ripples in intermediate hippocampus. Purandare and Mehta, 2023 analyzed the responses of hippocampal neurons to natural movies and found that many displayed highly selective ‘movie fields’ that were often as robust as those of neurons in visual cortex.…”
Section: Three Families Of Use Casesmentioning
confidence: 99%